Labor Inclusion of Women in Public Administration - Torres Rodas, María Augusta; Ormaza Ávila, Diego Adrián; Torres Rodas, David Fernando (Scientific journal of social studies, 2024)
This study investigates the employment inclusion of women in public institutions within the province of Cañar, Ecuador, focusing particularly on the equitable allocation of managerial positions. Utilizing a quantitative approach, historical methods were employed to delineate the evolution of women’s labor rights, alongside analytical methods to assess current data from five selected public institutions. The findings reveal variability in gender representation: men predominate in terms of overall employment and in managerial roles in three out of five institutions. However, in the education sector and the hospital examined, women not only constitute the majority of the workforce but also predominantly occupy senior positions. These results suggest that while progress towards gender equity has been made in some areas, significant gaps remain that require targeted attention and renewed government policy efforts. This analysis underscores the necessity for more robust and effective policies to promote true gender equity in public administration, not only to uphold social justice principles but also to enhance administrative effectiveness and social development. The equitable inclusion of women at all levels of public administration is presented as both an ethical imperative and an urgent need for comprehensive societal progress.